Anna Lutkajtis, The Dark Side of Dharma: Meditation, Madness and Other Maladies on the Contemplative Path - Crotty, Robert (Journal for the Academic Study of Religion, 2022)
Anna Lutkajtis, The Dark Side of Dharma: Meditation, Madness and Other Maladies on the Contemplative Path, London: Aeon Books, 2021, pp. 182, ISBN: 13-9781913504595 (pbk). £18.99.